العوامل المؤثرة في رغبة الطلاب بتعلم اللغة العربية (الدراسة الحالة في مدرسة منهاج السلام الثانوية الأهلية تانجونج سلامات برجوت سي توان) - Syafrianda Syafrianda; Zulheddi Zulheddi (Al-Risalah : Jurnal Studi Agama dan Pemikiran Islam, 2024)
قلة الرغبة بالتعلم هي إحدى مشكلات تعلم اللغة العربية التي يجب التغلب عليها. كان الهدف من هذه الدراسة هو معرفة العوامل التي تؤثر على رغبة الطلاب بتعلم اللغة العربية. منهجية البحث التي أجريت هي نوعية مع نهج دراسة الحالة. كانت تقنيات جمع البيانات المستخدمة في هذه الدراسة هي المقابلات والملاحظة والتوثيق. أظهرت النتائج أن العوامل التي تؤثر على رغبة الطلاب بتعلم اللغة العربية تنقسم إلى عوامل داخلية وخارجية. تشمل العوامل الداخلية الرغبة بالتعلم والراحة في التعلم والرغبة في التعلم ومشاركة الطلاب. بينما تشمل العوامل الخارجية الخلفية التعليمية وطرق تدريس المعلمين والبيئة المدرسية والأسرية والقدرة على قراءة القرآن. Low interest in learning is one of the problems of learning Arabic that must be overcome. The purpose of this research is to find out what factors influence students' interest in learning Arabic. The research method used was qualitative with a case study approach. The data collection techniques used in this research were interviews, observation, and documentation. The research results show that the factors that influence students' interest in learning Arabic are divided into internal and external factors. Internal factors include a feeling of interest when learning, a feeling of comfort when learning, a desire to learn and student participation. Meanwhile, external factors include educational background, teacher teaching methods, school and family environment, and the ability to read the Quran